Effect of Public Debt on Economic Growth in Nigeria with or without Domestic Investment - Fasoye, Kazeem; Olayiwola, Abiodun Sunday (NIU Journal of Social Sciences, 2024)
The paper examines the effect of public debt on economic growth in Nigeria with or without domestic investment between 1981 and 2020 using a technique of Dynamic Least Square (DOLS). The findings of the study reveal that public debt in Nigeria retards economic growth through reduction in the level of investment. This indicates the possibility that the current levels of public debt in the Nigeria might not have been reducing the volume of growth but have the tendency to create a poorer macroeconomic and uncertain climate for investment. The implication is that the nonlinear relationship between debt and economic growth is a reality. It is suggested that there should be big push investment into all sectors of the economy that serve as engine of growth to the nation and whenever public debt is acquired, domestic investment must be given priority. Keywords: Effect, Public Debt, Economic Growth, Domestic Investment, Nigeria